1988 - 1968 De la Transición al largo '68 en Chile - Estefane, Andrés J.; Olmedo, Carolina C.; Thielemann, Luis H. (Ariadna Ediciones, 2019)
Historical and political analysis of the Chilean cycle 1968-1988, an era that marked the outstanding of contemporary Chilean society